2022
DOI: 10.1177/00333549221085238
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Previous COVID-19 Infection, COVID-19 Vaccination Receipt, and Intent to Vaccinate Among the US Workforce

Abstract: Objective: As COVID-19 vaccines become more accessible to all people in the United States, more employees are returning to the workforce or switching to in-person work. However, limited information is available on vaccination coverage and intent among the US workforce. Methods: We used data from the US Census Bureau’s Household Pulse Survey, fielded during April 14–May 24, 2021 (N = 218 787), to examine the prevalence of previous COVID-19 infection, vaccination receipt, and intent to vaccinate by essential wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…(2022) and Nguyen et al. (2022a, b), there is a robust difference in COVID-19 vaccination willingness between entrepreneurs and employees, which has now been confirmed in five datasets. Entrepreneurs consistently report lower COVID-19 vaccination intention and COVID-19 vaccination status than employees.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…(2022) and Nguyen et al. (2022a, b), there is a robust difference in COVID-19 vaccination willingness between entrepreneurs and employees, which has now been confirmed in five datasets. Entrepreneurs consistently report lower COVID-19 vaccination intention and COVID-19 vaccination status than employees.…”
Section: Discussionmentioning
confidence: 62%
“…To our initial surprise, two earlier studies showed that COVID-19 vaccination willingness was lower among self-employed individuals than among employees in a Belgian and US sample (Nguyen et al. , 2022a, b; Valckx et al. , 2022).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations